Strategi Manajemen Hubungan Masyarakat Sebagai Upaya Meningkatkan Mutu Pendidikan - Masrufa, Binti (At Tadbir: Islamic Education Management Journal, 2024)
This research aims to describe appropriate public relations management (PR) strategies to improve the quality of education at MTs Darussalam Ngoro Jombang. The research method used is qualitative with a descriptive analytical approach. The data collection techniques used were observation, interviews and documentation. The research results show that the right public relations strategy to improve the quality of education at MTs Darussalam Ngoro Jombang is creating an informative and attractive madrasah website, utilizing social media to promote the madrasah, holding interesting activities for the community, and building good relationships with alumni. The implementation of Public Relations strategies at MTs Darussalam Ngoro Jombang has been quite effective in improving the quality of education. This is evidenced by the increasing number of new students, increasing student achievement, and increasing the image of madrasas in society.